Renewable-load matching dispatch for isolated power systems with intermittent renewable sources. (2016) - Shen, Ying; Zhao, Qianchuan; Li, Mingyang
This paper proposes a renewable-load matching approach for dispatching generation resources in power systems with high renewable power penetrations. In order to utilise the capability of renewable resources to follow the load variations, the proposed matching approach is to restrict the output of renewable generators by a load-related bound in each dispatch time period. The dispatch problem is formulated to minimise the system cost comprising fuel, emission, and regulation costs as well as renewable power curtailment penalty. Compared with the traditional approach of treating renewable resources as negative loads, the proposed matching approach can significantly reduce the system cost by including the dynamic control of renewable power output. Moreover, the multi-objective function provides a way to study the trade-off among different costs in power systems with renewable resources. Solution is obtained by transforming the optimisation problem into its equivalent form and using local search algorithms. Simulations are implemented on a specific isolated power system with four generators to demonstrate the advantage of proposed approach.